Effects of Fermented Wheat Bran on Flour, Dough, and Steamed Bread Characteristics. (19th June 2018) - Li, Li; Wang, Zhen; Li, Li-Min; Zheng, Xue-Ling; Ma, Sen; Wang, Xiao-Xi
Abstract : Wheat bran is rich in dietary fiber, which improves the flour nutritional content and also endows the flour with a richer flavor. However, a high content of insoluble dietary bran fiber can easily and significantly reduce the processing and edible quality of flour products. This study was conducted to explore ways to decrease the negative effects of adding bran to dough. Basidiomycete strain BS-01 was used to ferment the wheat bran. The surface structure of the bran was examined by scanning electron microscopy, and the fermented bran was incorporated into the wheat flour at various concentrations. The mixed flour farinographic and extensographic characteristics, dough rheological properties, and the specific volume, color, and textural properties of the steamed bread were determined and analyzed. The results suggested that adding an appropriate quantity of fermented bran improves the characteristics of the dough and the quality of the steamed bread compared to those with unfermented bran. The fermented bran effectively decreased the negative impacts exerted on the farinographic and extensographic characteristics of the mixed flour and exerted a positive influence on the dough viscoelasticity and bread specific volume.